Synthesis, spectroscopic characterization and biological activity of macrocyclic copper (II) complex: Anti-bacterial activity against multi – Drug resistant bacteria - SANCHITA RAI; SHAILENDRA SEN; RICHA KOTHARI (International Journal of Pharma and Bio Sciences, 2019)
Transition metal compounds with macrocyclic Schiff base ligand representing an important class of antimicrobial compounds would be used to develop novel metal based antimicrobial agents and as precursors of biologically important copper complexes. In the present study copper complex of macrocyclic Schiff base ligand and its conjugate with Vancomycin drugs were synthesized by the refluxing method in absolute ethanol at 700 c. Also, we reported the modified and quick method for the preparation of vancomycin loaded copper (II) complexes. All synthesized compounds were characterized by analytical techniques, elemental analysis, TEM, powdered XRD, molar conductance measurement and various spectroscopic techniques like UV-Vis., FT-IR, TGA & DSC. The thermal behavior of the synthesized compounds explained the general decomposition patterns of the compounds. Additionally, invitro antibacterial activity of Schiff base ligand, its Cu (II) complex and Vancomycin loaded copper complex were tested against gram positive and gram negative bacteria E.coli (MTCC-1563), S. aureus (MTCC-3160) and Enterofaecalis (MTCC- 439) which explained the minimum inhibitory concentration values lower than those of previous reported values. This study revealed that some antimicrobial agents like Vancomycin can be conjugated with copper complex of macrocyclicschiff base ligand. This can be lead to increased antimicrobial activity against MDR microorganisms.